A targeted sequencing panel identifies rare damaging variants in multiple genes in the cranial neural tube defect, anencephaly. Issue 4 (11th February 2018) - Ishida, M.; Cullup, T.; Boustred, C.; James, C.; Docker, J.; English, C.; ,; Lench, N.; Copp, A.J.; Moore, G.E.; Greene, N.D.E.; Stanier, P.
Abstract : Neural tube defects (NTDs) affecting the brain (anencephaly) are lethal before or at birth, whereas lower spinal defects (spina bifida) may lead to lifelong neurological handicap. Collectively, NTDs rank among the most common birth defects worldwide. This study focuses on anencephaly, which despite having a similar frequency to spina bifida and being the most common type of NTD observed in mouse models, has had more limited inclusion in genetic studies. A genetic influence is strongly implicated in determining risk of NTDs and a molecular diagnosis is of fundamental importance to families both in terms of understanding the origin of the condition and for managing future pregnancies. Here we used a custom panel of 191 NTD candidate genes to screen 90 patients with cranial NTDs ( n  = 85 anencephaly and n  = 5 craniorachischisis) with a targeted exome sequencing platform. After filtering and comparing to our in‐house control exome database ( N  = 509), we identified 397 rare variants (minor allele frequency, MAF < 1%), 21 of which were previously unreported and predicted damaging. This included 1 frameshift ( PDGFRA ), 2 stop‐gained ( MAT1A ; NOS2 ) and 18 missense variations. Together with evidence for oligogenic inheritance, this study provides new information on the possible genetic causation of anencephaly. Abstract :